Facile synthesis of carbon dot-Au nanoraspberries and their application as high-performance counter electrodes in quantum dot-sensitized solar cells. (January 2016) - Dao, Van-Duong; Kim, Poeun; Baek, Seunghyeon; Larina, Liudmila L.; Yong, Kijung; Ryoo, Ryong; Ko, Seung Hyeon; Choi, Ho-Suk
Abstract: Carbon dot-Au nanoraspberries (Cdot-Au NRs) were synthesized by a simple one-pot process using Cdots as initiators to direct the dendritic growth of Au via room temperature chemical reduction of HAuCl4 by formic acid. We evaluated the resulting Cdot-Au NR as a counter electrode material for ZnO nanowire/CdS/CdSe quantum dot-sensitized solar cells (QDSCs). The counter electrode employing Cdot-Au NRs exhibited higher electrocatalytic activity, lower charger-transfer resistance, and larger exchange current density than commonly used Au-sputtered counter electrodes. The power conversion efficiency of the cell was improved to 5.4%, in comparison to efficiencies of 3.6% and 0.18% shown by cells employing Au-sputtered and Cdot counter electrodes, respectively. These features render Cdot-Au NRs as highly promising counter electrode materials for QDSCs.